2007
DOI: 10.1111/j.1365-2141.2007.06766.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thromboembolism in 14 000 individuals with coeliac disease

Abstract: Summary The risk of venous thromboembolism (VTE) was examined in individuals with coeliac disease (CD). The Swedish national inpatient register was used to identify 14 207 individuals with a diagnosis of CD (1964–2003). These individuals were matched for age, sex, calendar year and county with 69 048 reference individuals. Cox regression was used to estimate hazard ratios (HRs) for subsequent thromboembolism in individuals with more than 1 year of follow‐up and no prior VTE. CD was associated with an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 47 publications
1
48
0
2
Order By: Relevance
“…An English registry-based study found an increased VTE rate among CD patients compared with a hospital comparison cohort [incidence rate ratio (IRR) = 1Á35, 95% CI: 0Á89-1Á97] (Ramagopalan et al, 2011). Similarly, a Swedish study of 14 207 adult CD patients followed for a median of 14 years, found an increased VTE rate (IRR = 2Á66, 95% CI: 2Á27-3Á11), especially in the year after diagnosis (Ludvigsson et al, 2007). An advantage of our study, compared with the previous studies, is that we adjusted for VTE risk factors, such as medication use and several comorbidities.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…An English registry-based study found an increased VTE rate among CD patients compared with a hospital comparison cohort [incidence rate ratio (IRR) = 1Á35, 95% CI: 0Á89-1Á97] (Ramagopalan et al, 2011). Similarly, a Swedish study of 14 207 adult CD patients followed for a median of 14 years, found an increased VTE rate (IRR = 2Á66, 95% CI: 2Á27-3Á11), especially in the year after diagnosis (Ludvigsson et al, 2007). An advantage of our study, compared with the previous studies, is that we adjusted for VTE risk factors, such as medication use and several comorbidities.…”
mentioning
confidence: 79%
“…deep vein thrombosis (DVT) and its complication pulmonary embolism (PE), because they are reported to have hyperhomocysteinaemia, low levels of K-vitamin-dependent anticoagulant proteins, and increased levels of thrombin-activatable fibrinolysis inhibitor (Halfdanarson et al, 2007). There are several case reports regarding VTE occurrence in CD patients (Daum et al, 2009;Halfdanarson et al, 2007), but observational studies present conflicting results and may have been confounded by medication use and several comorbidities (Ludvigsson et al, 2007;Miehsler et al, 2004;Ramagopalan et al, 2011).…”
mentioning
confidence: 99%
“…The final link was made by including data from the Swedish Hospital Discharge Register, which records complete information on all discharges with dates of hospitalization and diagnoses since 1986. The centralized Swedish Patient Registry has a very high coverage [30], and its scientific value has been confirmed in a number of studies, including those of VTE [31][32][33]. All linkages were made by using the unique individual national identification number assigned to each person in Sweden.…”
Section: Methodsmentioning
confidence: 99%
“…In the presented case the site of venous thrombosis was the extremity as an extremely rare localization. The study by Ludvigsson et al had shown a significant, positive association between CD and venous thromboembolism (10). The exact causes of thrombosis in patients with CD are yet unknown, but in some cases thrombosis has been attributed to acquired hyperhomocysteinemia as a concequence of folic acid and vitamin B12 deficiency (11).…”
Section: Discussionmentioning
confidence: 99%